Enhancement of the corrosion resistance of Molybdenum by La2O3 dispersion. (1st July 2021) - Cairang, Wande; Li, Tianshu; Xue, Dezhen; Yang, Hejie; Cheng, Pengming; Chen, Can; Sun, Yuanjun; Zeng, Yi; Ding, Xiangdong; Sun, Jun
Highlights: The addition of La2 O3 improves the corrosion resistance of Molybdenum (Mo) in 3.5 wt.% solution. A compact and protective oxide film forms with the introduction of La2 O3 into Mo. The refinement of grain size and the purification of impurity elements due to La2 O3 enhance the corrosion resistance. Abstract: The corrosion behavior of pure Molybdenum (Mo) and Mo doped with 0.3 wt. % La2 O3 was investigated in aerated 3.5 wt. % NaCl at 25 °C. Compared with the pure Mo, the doped Mo exhibits significantly increased corrosion resistance, with a smaller current density during anodic polarization and a 2∼3 times larger charge transfer resistance. Such an enhancement originates from the refinement of grains and purification of the grain boundary due to the addition of La2 O3, which facilitates the formation of a compact and protective oxide film. Our results provide a recipe to improve the corrosion resistance of Mo alloys.